MENINJAU ULANG SISTEM PILKADA LANGSUNG: MASUKAN UNTUK PILKADA LANGSUNG BERKUALITAS - FITRIYAH, FITRIYAH (Politika: Jurnal Ilmu Politik, 2011)
AbstractGovernors/bupaties/mayors had previously been elected by DPRDs, but a 2004 law onregional elections mandated that they be elected through direct popular vote. In practice, under thatsystem raising widespread skepticism caused by some problems as such, holding direct electionshave been too costly, high violations and conflicts, and unsuccessful raising strong leader. In fact thevarious direct local election problems are mainly related to loophole in written and unwritten electionrules. Hence, direct elections are still relevant and no need to eliminate and return to the pastsystem. Suggested the government and the House have should revise a 2004 law on regionalelections as such bribes for votes, high cost for hold and prone to trigger conflicts could beminimized.Keywords: sistem pilkada, beban anggaran, intensitas konflik, kualitas pilkada